Collaborative Systems for Reindustrialization c - Camarinha-Matos, Luis M.; Scherer, Raimar J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 14th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2013, held in Dresden, Germany, in September/October 2013. The 75 revised papers were carefully selected for inclusion in this volume. They provide a comprehensive overview of identified challenges and recent advances in various collaborative network (CN) domains and their applications with a particular focus on the support for reindustrialization. The papers have been organized in the following topical sections: product-service ecosystems; innovation in networks; strategies to build collaborative networks; collaboration related processes and performance; models and meta-models of collaboration; cloud-based support to collaborative networks; collaborative platforms; services and service design; sustainable collaborative networks; event-driven collaborative networks; social-semantic enterprise; and risks and trust.
Product-service ecosystems -- Innovation in networks -- Strategies to build collaborative networks -- Collaboration related processes and performance -- Models and meta-models of collaboration -- Cloud-based support to collaborative networks -- Collaborative platforms -- Services and service design -- Sustainable collaborative networks -- Event-driven collaborative networks -- Social-semantic enterprise -- Risks and trust.
Keywords: Computer science; Computer Communication Networks; Information systems; Information Systems; Management information systems; Computer Science; Management of Computing and Information Systems; Computer Appl. in Administrative Data Processing; Business Information Systems; Information Systems Applications (incl. Internet).; Computer Communication Networks